Perceived Barriers of Child Immunization among Mothers of Under-5 Children in Urban Slum of Ludhiana City - Harjot Kaur; Vikram Kumar Gupta; Anurag Chaudhary; Sangeeta Girdhar; Priya Bansal; Surinderpal Singh (Medsci Publications, 2019)
Introduction: In India, due to some barriers, the parents are not willing to vaccinate their children which lead to 3.2 million of chil- dren still not being vaccinated. Materials and Methods: A descriptive study was conducted on 200 mothers of under-five children residing in filed practice area of UHTC, Shimlapuri. Structured interview questionnaire was ap- plied on mothers to explore the knowledge on immunization & perceived barriers related to it. Results: The study revealed that 50.5% of mothers of under-five children were having below average level of knowledge on child immunization. Child illness and low importance of vaccination were most occurring perceived barriers among mothers. There were other barriers like lack of accompany to go to center for im- munization, and confusion about what age immunization has to be given, etc. Conclusion: Current study necessitates the need to to provide IEC (information, education and communication) sessions programs. This can be achieved by organizing health education campaigns in community. Parents and families need to be sensitized regarding importance of immunization to overcome the perceived barriers.